Association of the phenylpropanoid pathway with dormancy and adaptive trait variation in apricot (Prunus armeniaca). (2nd July 2019) - Conrad, Anna O; Yu, Jiali; Staton, Margaret E; Audergon, Jean-Marc; Roch, Guillaume; Decroocq, Veronique; Knagge, Kevin; Chen, Huadong; Zhebentyayeva, Tetyana; Liu, Zongrang; Dardick, Christopher; Nelson, C Dana; et al.
Abstract: Trees use many mechanisms to adapt and respond to stressful conditions. The phenylpropanoid pathway in particular is known to be associated with a diverse suite of plant stress responses. In this study, we explored the relationship between the phenylpropanoid pathway metabolite production, gene expression and adaptive trait variation associated with floral bud reactivation during and following dormancy in Prunus armeniaca L. (apricot). Concentrations of eight phenylpropanoid metabolites were measured during chill accumulation and at developmental stages corresponding to the emergence of sepals and petals in floral buds of varieties that differ phenotypically in bloom date (BD). A significant interaction effect of chill hours and BD phenotype on the concentration of each of the compounds was observed (mixed analysis of variance, P < 0.05), with the concentration of most phenylpropanoid metabolites dropping precipitously when sepals and petals emerged. While phenylpropanoid biosynthetic gene expression patterns were more variable in general, expression changed over time and was impacted, although to a lesser degree, by BD phenotype. Furthermore, separation of BD phenotypic groups was most pronounced when early and late BD varieties were at different developmental stages, i.e., 800 chill hours. Taken together, these results suggest that the phenylpropanoid pathway is associated with floral bud reactivation in apricot . Furthermore, we show that the phenylpropanoid pathway is also impacted by phenological trait variation associated with dormancy. A better understanding of how apricot and other perennial tree species respond and adapt to environmental perturbations will be critical for improvement programs aimed at identifying and breeding trees more suitable for rapidly changing environments.